325 Myeloid Sarcomas and Concurrent Bone Marrow Biopsies May Demonstrate Discordant Mutational Profiles by Massively Parallel Sequencing. (11th January 2018) - Werstein, Brian; Dunlap, Jennifer; Cascio, Michael; Ohgami, Robert; Fan, Guang; Press, Richard; Raess, Philipp
Abstract: Introduction: Myeloid sarcoma (MS) is a rare architecture-effacing proliferation of myeloid blasts at an extramedullary site. Few studies have compared the mutational profile of MS and concurrent bone marrow biopsy (BMBx) specimens by massively parallel sequencing. Methods: Five cases of MS were retrospectively identified with a BMBx within one month of diagnosis and molecular testing of both specimens. All BMBx and four of the MS cases were evaluated by targeted massively parallel sequencing to identify mutations frequent in myeloid neoplasms. Sanger sequencing was used to evaluate the fifth MS. Results: All cases of MS demonstrated pathogenic mutations. Four cases had morphologically unremarkable concurrent BMBx. Three cases demonstrated discordant findings between the MS and BMBx. In one discordant case, both the MS and morphologically unremarkable BMBx demonstrated a pathogenic NRAS G13R at high mutant allele frequency (MAF). A second discordant case showed 10 mutations in the MS; the morphologically unremarkable BMBx demonstrated only partial mutation overlap with four common mutations and an additional TP53 mutation at low MAF. A third discordant case demonstrated a BMBx involved by a myeloproliferative neoplasm with increased blasts and a JAK2 V617F, but the MS had an NPM1 mutation and no JAK2 V617F. The two remaining cases demonstrated morphologically unremarkable BMBx without mutations. Conclusion: Mutations were identified in all five MS. Three BMBxs demonstrated discordant mutation profiles. Interestingly, two of these discordant cases demonstrated somatic mutations in the BMBx despite absence of morphologic disease. Further investigation into molecular discordance between MS and BMBx is warranted.